Acts of the Apostles: an exegetical and contextual commentary - Immanuel, Babu (India commentary on the New Testament, 2017)
Introduction -- Commentary: Acts 1 : Resurrection, the reason to be -- Acts 2 : the Holy Spirit : the power to be witnesses -- Acts 3 : What's in a name? -- Acts 4 : no other name! -- Acts 5 : counterattacks -- Acts 6 : division and Diakonia -- Acts 7 : Stephen's speech -- Acts 8 : the gospel to the fringe people by a fringe man -- Acts 9 : the conversion of Saul -- Acts 10 : the household conversion of Cornelius -- Acts 11 : Peter's Apologia and the anonymous missionaries -- Acts 12 : irony : the predator becomes the prey -- Acts 13 : Paul's first missionary journey -- Acts 14 : Paul's first missionary journey continued -- Acts 15 : The Jerusalem Council -- Acts 16 : the second missionary journey -- Acts 17 : the gospel reaches Macedonia and Greece -- Acts 18 : Paul in Corinth -- Acts 19 : Paul's third missionary journey -- Acts 20 : through Macedonia and Greece to Jerusalem -- Acts 21 : O, Jerusalem! -- Acts 22 : Paul, an impeccable Jew -- Acts 23 : Resurrection, the 'X' factor -- Acts 24 : This one thing...Resurrection -- Acts 25 : I appeal to Caesar -- Acts 26 : the Messiah, the first to rise from the dead -- Acts 27 : so long, Paul! -- Acts 28 : St. Paul's bay : Rome, the new home!